Managing the Real and Fiscal Effects of Banking Crises - Klingbiel, Daniela; Laeven, Luc (Washington, DC: World Bank, 2013)
The study provides two recent analyses, spurred by the recent East Asian crisis, of government responses to financial distress, and, also presents a comprehensive database on systemic, and borderline banking crises. In the first chapter, the authors review the tradeoffs involved in public policies for systemic, financial, and corporate sector restructuring. They find that consistent policies are crucial for success, though such consistency is often missing. This consistency covers many dimensions, and entails among other things, ensuring that there are sufficient resources for absorbing losses, and, that private agents face appropriate incentives for restructuring. The authors also find that sustainable restructuring, requires deep structural reforms, facing upfront, political economy factors. In the second chapter, the authors use cross-country evidence to determine whether specific crisis containment, and resolution policies, systematically influence the fiscal costs of resolving a crisis. They find that accommodating policies - such as blanket deposit guarantees, debtor bailouts, and regulatory forbearance, etc. - significantly increase fiscal costs. The third chapter, is a comprehensive database on systemic banking crises that have occurred since the late 1970s. The database also includes information on borderline (non-systemic) banking crises during the same period.